2023
DOI: 10.1371/journal.pone.0290977
|View full text |Cite
|
Sign up to set email alerts
|

Identifying indicators sensitive to primary healthcare nurse practitioner practice: A review of systematic reviews

Kelley Kilpatrick,
Eric Tchouaket,
Isabelle Savard
et al.

Abstract: Aim To identify indicators sensitive to the practice of primary healthcare nurse practitioners (PHCNPs). Materials and methods A review of systematic reviews was undertaken to identify indicators sensitive to PHCNP practice. Published and grey literature was searched from January 1, 2010 to December 2, 2022. Titles/abstracts (n = 4251) and full texts (n = 365) were screened independently by two reviewers, with a third acting as a tie-breaker. Reference lists of relevant publications were reviewed. Risk of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…In essence, the review of systematic reviews describes the literature related to advanced practice nursing globally to identify key research gaps. The methods used in an umbrella review of indicators sensitive to primary healthcare NP practice formed the basis for the current review [ 9 , 17 ]. The descriptive table, critical appraisal and outcomes table are presented in the appendices given the large size of these tables.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In essence, the review of systematic reviews describes the literature related to advanced practice nursing globally to identify key research gaps. The methods used in an umbrella review of indicators sensitive to primary healthcare NP practice formed the basis for the current review [ 9 , 17 ]. The descriptive table, critical appraisal and outcomes table are presented in the appendices given the large size of these tables.…”
Section: Methodsmentioning
confidence: 99%
“…The full preliminary search strategy developed for the PubMed database was subsequently adapted to each electronic database (See S2 Appendix ). We adapted strategies reviewed by an academic librarian that have been used successfully in previous reviews [ 9 , 25 ]. In addition, hand searches of reference lists of all relevant reviews were conducted to identify additional studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a recent review of systematic reviews of indicators sensitive to the practice of PHCNPs (n = 44 reviews), identified few systematic reviews focused on understanding how PHCNPs influence patient outcomes in home care services. 5…”
Section: Introductionmentioning
confidence: 99%
“…29 There is little literature on the implementation of PHCNPs in home care. 5 Home care teams that include PHCNPs demonstrate greater effectiveness in reducing service utilization and achieve comparable or improved outcomes in prevention and screening compared to teams without PHCNPs. 24,30 Chavez et al 24 showed that home care provided by PHCNPs improves physical function and reduces falls and hospital admissions, thereby helping to prolong patients' independence at home and improve their quality of life.…”
Section: Introductionmentioning
confidence: 99%